2023
DOI: 10.1037/trm0000379
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of childhood trauma, intimate partner violence, and other traumatic life events on complex posttraumatic stress disorder symptoms.

Abstract: Complex posttraumatic stress disorder (CPTSD) follows persistent and repeated trauma and is a serious mental health problem among women. One of the strongest predictors of CPTSD symptoms is childhood trauma, especially child abuse and neglect, both of which are traumas that tend to be persistent and repeated. CPTSD is also associated with intimate partner violence (IPV; physical, emotional, and/or sexual violence in an intimate relationship), a trauma that, similar to child abuse and neglect, is also persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Findings suggest that for all people, interpersonal trauma, including but not limited to betrayal trauma, was associated with complex PTSD symptoms. This is consistent with the theory that complex PTSD is a result of interpersonal trauma, although this is truer for women than men (Cloitre et al, 2009; Gallagher et al, 2022). One reason for men having a broader range of traumas associated with complex PTSD symptoms is that men (at least in this sample) experienced more (nonbetrayal) interpersonal and noninterpersonal traumas than women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Findings suggest that for all people, interpersonal trauma, including but not limited to betrayal trauma, was associated with complex PTSD symptoms. This is consistent with the theory that complex PTSD is a result of interpersonal trauma, although this is truer for women than men (Cloitre et al, 2009; Gallagher et al, 2022). One reason for men having a broader range of traumas associated with complex PTSD symptoms is that men (at least in this sample) experienced more (nonbetrayal) interpersonal and noninterpersonal traumas than women.…”
Section: Discussionsupporting
confidence: 90%
“…Complex PTSD captures the diagnostic complexity following traumas beyond the narrow scope of what is included in a PTSD diagnosis such as chronic and repetitive traumas (Courtois, 2008;Ford & Courtois, 2020;Herman, 1992). Consistent with this, research suggests that traumas that tend to be prolonged and recurring (e.g., childhood abuse, intimate partner violence) are associated with complex PTSD symptoms over and above other traumas that tend to occur in isolation (e.g., vehicular accidents; Cloitre et al, 2009;Gallagher et al, 2022). However, there are other ways to think about differential trauma severity.…”
mentioning
confidence: 94%
“…However, in this study, we modified the LEC-5 by changing the rating anchors to a 5-point scale to assess the number of experiences (ranging from zero to four or more times ), and therefore the frequency of trauma experienced. Research suggests that the LEC-5 with modified scoring has high internal consistency (α = .93) and strong criterion validity with respect to complex PTSD symptoms (see Gallagher et al, 2022). We asked participants to focus on experience during their time in the military only.…”
Section: Methodsmentioning
confidence: 99%
“…These findings are consistent with a robust literature on the influence between personality traits and posttraumatic psychopathology, with neuroticism having the strongest (positive) effect and agreeableness and extraversion having smaller (negative) effects of PTSD and related problems (Kotov et al, 2010; for review, see Lahey, 2009; Sauer-Zavala & Barlow, 2021). However, the differential influence of personality traits on posttraumatic cognitions with respect to military trauma has not yet been examined (see Gallagher et al, 2022; Yalch et al, 2021 for studies on the influence of personality on posttraumatic cognitions in women exposed to intimate partner violence and sexual assault, respectively).…”
Section: Influence Of Trauma and Personality On Posttraumatic Cognitionsmentioning
confidence: 99%
“…Childhood trauma is often correlated with insecure attachment styles (Bederian-Gardner et al, 2018;Cooke et al, 2019;Ensink et al, 2020;Murase et al, 2021;Widom et al, 2018), and insecure attachment styles elevate the risk for a broad range of psychological disorders and somatic syndromes in adults (Alonso et al, 2018;Bo, & Kongerslev, 2017;Green et al, 2017;McWilliams, 2017). This line of research has identified the cumulative effects of trauma in adults resulting from repeated abuse and neglect and increasingly defined them as a distinct type of Developmental and Complex Trauma Gallagher et al, 2022;Karatzias et al, 2021;Musicaro et al, 2019;van Dijke et al, 2018) that is associated with traumatic interruptions during sensitive developmental periods.…”
Section: Evaluation Of Factor Structure and Measurement Invariancementioning
confidence: 99%